Along the waterline : cameraless photography and the haptic register of nocturnal seaborne activity : an exegesis submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy, Creative College of Arts Toi Rauwhārangi, Massey University, Wellington, New Zealand - Miles, Kevin (Massey University, 2022)
This creative practice research shifts the cameraless image from being an imponderable visual media already associated with experiential ’essences’ of the sea from land or shoreline perspectives; to an assertive document associated with the tangible, processual and material notion of a seaborne place experience. Using a methodology in which haptic qualities and processes extend the field of cameraless photography as a post-phenomenological aesthetic, I engage the skinlike sensitivity of photographic materials to the place phenomena and materiality of seaborne sites and activities. My research explores the aesthetic and ecstatic potential of cameraless photography, not as a critique of ‘the everyday’ as a concern, but as a retromodernist application of photography’s potential to defamiliarise the everyday. This attention to the common quality of things, and thus to perception and experience, grounds my study in critical phenomenological aesthetics. This approach of defamiliarisation underpins a unique cameraless interrogation of photography; to provoke and register a latent ecstasis harboured in ‘everyday’ seaborne experience. The research has consequently developed a methodology to confirm whether cameraless photography can be redefined in these terms. I revise a standard photographic form by presenting a unique set of socio-autobiographical, critical circumstances and methods, enhanced by living aboard a sailing vessel. By extending previous and current enquiries beyond their traditional terrestrial limits, I expand contemporary understanding of how cameraless photography can be defined as a post-phenomenological aesthetic.
Listed in 2022 Dean's List of Exceptional Theses
Keywords: Photography, Abstract; Photograms; Sea in art; Experiential research; Dean's List of Exceptional Theses; Dean's List of Exceptional Theses; 360699 Visual arts not elsewhere classified